2013
DOI: 10.4314/ahs.v13i3.19
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in Nigerians with essential hypertension

Abstract: Background: Reports on the association between hypertension and insulin resistance have been inconsistent even though most studies show a definite association. It is also not certain if the association between insulin resistance and hypertension applies to all populations. Objective: To determine the prevalence of insulin resistance in hypertensive Nigerians and to examine the association of insulin resistance with hypertension and some anthropometric indices. Methods: Thirty five adults with essential hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…The first is that body composition estimated by bioelectrical impedance showed a high frequency of visceral fat accumulation in hypertensive vs normotensive patients in a South-Kivu population. Moreover, although Saad MF et al reported that the association between blood pressure and insulin resistance was limited to Caucasians and absent among blacks and PIMA Indians [ 12 ], the present observation suggests a role for excess visceral fat (and insulin resistance) in the pathogenesis of arterial hypertension in black subjects corroborating other authors [ 25 ]. We noted, however, that another study reported a lack of correlation between blood pressure and insulin resistance in diabetic patients [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…The first is that body composition estimated by bioelectrical impedance showed a high frequency of visceral fat accumulation in hypertensive vs normotensive patients in a South-Kivu population. Moreover, although Saad MF et al reported that the association between blood pressure and insulin resistance was limited to Caucasians and absent among blacks and PIMA Indians [ 12 ], the present observation suggests a role for excess visceral fat (and insulin resistance) in the pathogenesis of arterial hypertension in black subjects corroborating other authors [ 25 ]. We noted, however, that another study reported a lack of correlation between blood pressure and insulin resistance in diabetic patients [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies demonstrated associations between hypertension [ 43 ], obesity [ 32 ], inflammation [ 44 ], lifestyle [ 45 ], and liver disease [ 46 ] and QTc prolongation. TyG index is reported to be a simple surrogate of insulin resistance [ 47 ], and numerous studies also found a relationship between insulin resistance and hypertension [ 48 , 49 ]. In an animal study, Lin et al [ 50 ] found that insulin resistant, obese, 16 to 17-week-old rats exhibited defective inactivation of current, altered electrophysiology characteristics, and developed cardiac hypertrophy due to a prolongation of QTc interval.…”
Section: Discussionmentioning
confidence: 99%
“…We found that hypertension combined with HTG can signi cantly increase the risk of developing hyperuricemia than any separate hypertension or HTG. Insulin resistance is partially overlapping pathophysiological features of dyslipidemia and hypertension [18][19][20][21]. Much researches have con rmed that insulin resistance was correlated with hyperuricemia [22,23].…”
Section: Discussionmentioning
confidence: 99%